PENGARUH KINERJA LINGKUNGAN TERHADAP PENGUNGKAPAN LINGKUNGAN DAN PENGUNGKAPAN LINGKUNGAN TERHADAP NILAI PERUSAHAAN - Fraditha Nira Artamelia, (2021)
This study aims to determine the effect of environmental performance on environmental disclosure and the effect of environmental disclosure on the firm value in the non-financial sector listed on the Indonesia Stock Exchange and follow the PROPER program in the period 2017 - 2019. The study used the stock price at the end of April t+1 as a measurement of the firm value. Environmental disclosure is measured using GRI G4 and GRI Standard, while environmental performance is measured with PROPER ratings. The type of this research is quantitative research that uses secondary data based on sustainability reports, financial reports and PROPER ranking lists. The sample in this study consisted of 28 companies in the non-financial sector. Hypothesis testing using multiple regression analysis with STATA version 16. The results of the data analysis in this study can be concluded that (1) environmental performance has a positive and significant effect on environmental disclosure; (2) environmental disclosure has a negative and significant effect on the firm value